The Crucial Role of Health Practitioners in Emergency Situations: A Comprehensive Review of Responsibilities, Interventions, Challenges, and Outcomes in Pre-Hospital and Clinical Emergency Care Settings - AL Dossary, Bashayer Draan,; AL Mutairi, Salma Salem,; AL Subaie, Mohammed Fawaz,; AL Mutairi, Meshari Mohammed,; AL Mutairi, Saad Saeed,; AL Mutairi, Sami Saud, (International Journal of Medical Toxicology and Legal Medicine, 2024)
Health practitioners play a critical role in managing emergency situations, both within pre-hospital settings and clinical emergency departments. Their responsibilities include initial assessment, rapid decision-making, patient stabilization, and coordination of care under highly stressful and often resource-constrained conditions. This comprehensive review synthesizes existing literature to explore the key roles and responsibilities undertaken by various health practitioners—including physicians, nurses, paramedics, emergency medical technicians (EMTs), and pharmacists—in emergency scenarios. It also examines the most prevalent and effective medical interventions performed, assessing their impact on patient outcomes and survival rates. Furthermore, the review highlights major operational, clinical, and psychological challenges faced by these professionals and analyzes strategies to overcome these issues. Key findings underscore the critical relationship between timely and effective interventions by skilled health practitioners and improved patient survival and quality of care. Finally, the article provides practical recommendations for enhancing emergency medical training, policy development, and resource allocation to strengthen practitioner preparedness and optimize emergency care delivery. Future research directions are proposed to fill current gaps and to continuously improve emergency response systems.